Rodríguez Melchor, María Dolores, Horváth, Ildikó and Ferguson, Kate (eds.), The Role of Technology in Conference Interpreter Training. New York: Peter Lang 2020. 245 pp. - Jamalimanesh, Alireza; Afrouz, Mahmoud (Estudios de Traducción, 2021)
Reseña de The Role of Technology in Conference Interpreter Training (New Trends in Translation Studies, Vol. 31), by María Dolores Rodríguez Melchor, Ildikó Horváth and Kate Ferguson (eds), New York, Peter Lang, 2020, 245 pp., ISBN 9781788744096